INTERNALISASI NILAI KEIMANAN DAN KETAKWAAN TERHADAP TUHAN YME DALAM PROSES PEMBELAJARAN PAI KELAS IV UNTUK MENCAPAI PROFIL LULUSAN DI SDN 158 PALEMBANG - Lisa Septiani; Muhamad Afandi; Miftahul Husni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study is motivated by the importance of internalizing faith and piety values in Islamic Religious Education (PAI) learning to support the achievement of the Graduate Profile, especially in aspects of faith, piety, and noble character. The purpose of this research is to describe the forms of internalization of faith and piety values in grade IV PAI learning, the role of teachers in the process, and its impact on the Graduate Profile. This research uses a descriptive qualitative approach with a case study design at SDN 158 Palembang. Data were obtained through interviews with PAI teachers and the principal, observation, and documentation, and analyzed using data reduction, data presentation, and conclusion drawing, with validity tested through source, technique, and time triangulation. The results show internalization occurs through religious habituation, value integration in learning, and routine school religious programs, while teachers contribute through planning, modeling behavior, habituation methods, and strengthening values in learning. This internalization increases worship habits, religious awareness, and students’ moral and social development. Thus, internalization of faith and piety in PAI learning contributes positively to Graduate Profile achievement in elementary schools, strengthening students’ religious character sustainably in line with national education goals and supporting Pancasila Student Profile implementation.